CORN SUBSTITUTION USING FERMENTED SOLID CASSAVA-WASTE ON BROILER CHICKEN - Ali-Mursyid, W.M.; Bachruddin, Z.; Zuprizal, Z.; Nur-Cahyanto, M. (Diponegoro University, 2010)
The objective of the research was to examine unfermented solid cassava-waste (USCW) andfermented solid cassava-waste (FSCW) as the substitution of corn in broiler ration. Two hundred and tenbirds of one-week-male broiler chicken were divided into seven kinds of one-way treatment ofcompletely randomized design. Five replications were used for each treatment; there were six chickensin each replication. The substitution levels of corn in broiler ration by USCW and FSCW were 0%(control), 10, 20, and 30%. The result showed that corn substitution up to 20% using USCW and FSCWdid not affect the digestibility of feed (DF), digestibility of soluble protein (DSP) and crude protein(DCP), and digestibility of starch (DS). Substitution up to 30% using FSCW did not affect the DSP andDCP. However, substitution of USCW at the same level decreased DSP, DCP, DF, and DS. Cornsubstitution up to 20% using USCW and FSCW did not affect the feed intake (FI), body weight gain(BWG) and feed conversion ratio (FCR). Substitution up to 30% using FSCW did not affect the BWGand FCR. However, substitution of USCW at the same level decreased BWG and increased FCR. FSCWcan be used as a substitute for the corn up to 30% without affecting the performance and the values ofthe nutrient digestibility, meanwhile USCW is only able to substitute corn up to 20%.